Current Status of the Genus Bryum Hedw.In Central India - Bansal, Pooja; Nath, Virendra (Indian Forester, 2016)
Bryum Hedw. is represented in Central India by fourteen species. Of these, B. pseudotriquetrum (Hedw.) P. Gaertn., B. Mey. et Scherb., reported from Amarkantak and B. pseudotriquetrum var. subrotundum (Brid.) Gangulee from Mount Abu (Rajasthan) are new record for Central Indian Bryoflora.